Ectopic thyroid cancer in the ovary – unresolved issues of diagnosis and treatment of struma ovaria maligna - O. O. Kovalyov; O. P. Tolok; K. O. Kovalov (Patologìâ)
Struma ovaria is an ectopic localization of mature thyroid gland tissue in the ovaries. This rare form of monodermal teratoma is mostly a benign pathology. Primary malignant tumors of the thyroid gland in the appendages of the uterus are represented by thyroid carcinomas. Due to the rare pathology (less than 1 % of all tumors), insufficient information in the literature, lack of generalized recommendations and personal experience, doctors make many mistakes during the treatment of patients with struma ovary.